Application Of The Rahn Contract In Islamic Pawnshops - Nurmansah; Bani Sarif Maula (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Pledge is stipulation and detention, rahn is collateral, collateral, reserves guarantees and dependent Islamic pawnshops apply the rahn main contract and use administrative fees according to the loan amount. The collateral remains the property of the person who mortgages it but is controlled by the pawnbroker. The operational pawn technique is carried out by a sharia institution. Addtional contract status, this research method uses the libary method, resulting in this research applying the rahn contract in accordance with Islamic law in accordance with sharia economic law